Cooperación como respuesta a la inseguridad marítima en el Pacífico Sur Oriental - Garay Cuesta, Francisco (Hemisferio - Revista del Colegio Interamericano de Defensa, 2021)
The coastal states of the Eastern South Pacific are affected by threats to maritime security, which act on various dimensions of the human security of their societies. In this article, present threats in these maritime spaces are characterized and the response of the countries is analyzed, to propose a scheme in which cooperation is presented as the best way to improve the situation, recommending the creation of an organization with state and extraregional actors, communities and non-state organizations that have participation in the issue, as part of the solution to the problem